Does the clackers balls toys Make a student’s behavior change? A literature review at elementary school - Teofilus Ardian Hopeman; Aulia Rahma (Westscience Press, 2023)
This study aims to identify and obtain information about parents' perspectives on clackers’ ball toy games (Clickers Balls) and whether they have an impact on behavior change or not. Currently, the clackers balls toys game is a game that is very loved in society by all ages, both young and old. Clacker’s ball toys game is a game in the form of two small balls or pendulums that are connected through a rope he plays simply by banging both balls using the palm until it makes a fairly loud sound with an up-and-down movement. Descriptive-qualitative research methods are used in this study that aiaimso provides an overview and expose information about something according to the conditions at the time. The data collection technique in this study was through interviews and observations at one of the elementary schools in Sukabumi, West Java. The results show that children who play clackers, tend to become more active in interacting and socializing considering that this game will be more exciting if played together. In addition, the increase in children's social interaction, itso reduces the intensity of children's use and dependence on gadgets. Therefore, if vitamins with good supervision from parents, this clackers toys game will help the child to improve his motor and cognitive abilities, as well as his ability to socialize.